AN INVESTIGATION OF LEARNER AUTONOMY AMONG INDONESIAN UNDERGRADUATE EFL STUDENTS - Melvina, _ (2022)
Despite the increasing number of research on learner autonomy (LA), little has been done to scrutinize the level of LA and its relationships to English proficiency, particularly in the Indonesian context. This study aims to investigate the autonomy level of Indonesian university students based on the four aspects of learner autonomy, explore how they learn English autonomously and examine the influence of the four aspects of learner autonomy on students' language proficiency. Using a mixed-method design, this study involved forty undergraduate students majoring in English education at a university in Bandung, Indonesia. A learner autonomy questionnaire was used to collect quantitative data which was then analyzed using descriptive statistics and Structural Equation Modeling Partial Least Square (SEM-PLS). Interviews and observation were conducted for more information in detail as qualitative data collection. The findings of this study showed that the undergraduate students were categorized into the mediate levels of autonomy. This indicated that Indonesian undergraduate students were considered somewhat autonomous learners. With the support of the lecturer, they can perform some autonomous learning behaviors in their learning such as setting goal, making a study plan, and evaluating the improvement of their English ability. It was also observed that the students had implemented autonomous learning when studying which signifies that the students had sufficient knowledge and skills of LA. Furthermore, the results of the analysis of SEM-PLS showed a robust correlation between LA and language proficiency. This research suggests English teachers to consistently promote LA in the classroom and calls for the importance of surveying students' levels of autonomy at the beginning of the academic year for the teacher to design their instruction to direct their students to learn autonomously by equipping students with LA training to develop learner autonomy and achieve greater levels of English proficiency